Onco-hematology: perspectives and advances - Silva, Hyan Ribeiro da (2020)
The present study observed to report the advances in Onco-hematology, an area that takes care of malignant blood diseases, these diseases require specific treatment, with advanced equipment and tests to take care of each one of these pathologies, ranging from blood tests to bone marrow transplants. Bone. During the work, we will analyze perspectives in the treatment of such diseases, seeking a better understanding of the importance of these studies. The trajectory of hemotherapy since the scientific era has been marked by changes in paradigms, that is, it begins with minimal importance, with rudimentary levels of technique, even having a certain monetization for those who donated. There was no concern as there is today regarding the detection of diseases through exams, everything was very precarious.